Alternative Bedding Materials for Poultry: Availability, Efficacy, and Major Constraints - Diarra, Siaka; Lameta, Sonny; Amosa, Falaniko; Anand, Sanjay (Frontiers in Veterinary Science, 2021)
The increasing demand of wood shavings (WS) and sawdust (SD) by other industries and growing concerns of potential chemical contaminants from wood products have amplified research interest in alternative bedding materials for commercial poultry. Several alternative materials: corn cob (CC), straws (ST) and hays (HA), sand (SA), shredded papers (SP), rice hulls (RH), peanut hulls (PH) and Gypsum (CaSO4 .2H2O2) can replace conventional ones in poultry houses, depending on availability, cost and ability to absorb and adsorb moisture and provide the birds enough room to exhibit their natural behaviours. Alternative materials hold brighter future as bedding materials but more studies in their physicochemical properties and litter management practices for optimum poultry welfare are recommended.